PERCERAIAN DALAM PERSPEKTIF TALCOTT PARSON TERHADAP KOMUNIKASI KELUARGA DAN KONDISI PSIKOSOSIAL ANAK - Reno Firdaus; Riana Wulandari; Syahadan; Tata Prayoga (Akademika : Jurnal Keagamaan dan Pendidikan, 2025)
Divorce within the family impacts social stability, particularly in the psychosocial development of children. According to Talcott Parsons' structural functionalism theory, the family functions to maintain stability through affection and socialization. However, divorce leads to disorganization within the family structure, disrupting the process of socialization and communication among family members. The decline in the quality of communication in post- divorce families affects the emotional and social development of children. This study employs a literature review approach to analyze existing literature related to divorce, family communication, and the psychosocial condition of children. The findings indicate that divorce results in fragmentation of family communication and imbalance in the socialization process, which increases the risk of psychosocial disturbances, such as anxiety and difficulties in forming healthy social relationships